The skepticism and belief in the work of Ch. Peirce - is a form of thinking (Journal of Philosophy Culture and Political Science, 2018)
This article reviews the book by Charles Peirce`sphilosophy of pragmatism and discusses the main problems:of logical thinking and scientific metod.